Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 94. Beitrag (Ephemeroptera). - Puthz, Volker (Contributions to Entomology = Beiträge zur Entomologie, 1980)
The expedition of Albania made in 1961 by Deutsches Entomologisches Institut collected 31 individuals of ten species of Ephemeroptera, eight species of which were recorded for the first from Albania. In addtion, the material in the Museum of Natural History in Vienna, collected by the expedition to Albania made in 1918, was examined and yielded eight other first finds in that country. Thus a total of 24 species of Ephemeroptera are now known from Albania. Additional material from the adjacent territories is published for the first time, and a general survey of the Ephemeroptera of the Balkan countries is given. Nomenclatural Actsalbanicus Puthz, 1980 (Ecdyonurus krueperi), sspec. n.